PERANCANGAN SISTEM APLIKASI DESKTOP PRODUKTIVITAS TIM VALIDASI PADA PERUSAHAAN MARKETING RESEARCH INDONESIA: Indonesia - Nur Ardhillah Zuhdi, Aisyah; Sonny, Michael; Fazrie, Mohammad (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2021)
Work productivity is the ability of employees to produce compared to the input used, an employee can be said to be productive if he is able to produce services in accordance with the expected time. The purpose of this study is to analyze the system that is running on the Validation Team. The research method used is the waterfall method to describe the running system and the design to be built. The method of analysis that the researcher uses is by conducting direct observations at the company, conducting research on problems, documentation by studying existing documents, and interviews with several parties involved in the Validation Team. Researchers get research results that the productivity management system is beneficial for companies, especially in the Validation Team. As for the benefits of increasing the performance of the Validation Team, the results of the information work produced will be more structured, accurate, and processing time becomes more effective. The conclusion of this research is the implementation of a productivity application system on the Validation Team, providing convenience in the work system, solving problems in recapitulating team work productivity data, and providing convenience in making the final productivity report..